Zoonoses in rural veterinarians in the central region of Argentina. (11th October 2013) - Molineri, Ana; Signorini, Marcelo L.; Pérez, Luis; Tarabla, Héctor D.
Abstract Objective To estimate the frequency of zoonoses in rural veterinarians and to search for risk factors. Design Cross‐sectional study based on an anonymously answered structured questionnaire. Setting The interviewees participated in mandatory continuing education classes scheduled throughout the province by the College of Veterinary Surgeons. Participants Overall, 741 professionals were surveyed, and 75.8% (n = 562) of them completed the structured questionnaire. Main outcome measures Cumulative incidence (CIR) and incidence density (IDR) rates, standardised rates, χ2, Student's t‐test, Pearson's correlation coefficient and logistic regression. Results The CIR for all zoonoses was 34.1% (brucellosis, 29.1%; toxoplasmosis, 2.1%; leptospirosis, 0.6%; tuberculosis, 0.6%; anthrax, 0.6%; ringworm, 0.4%; other, 0.6%). The IDR for the period 1964–2008 was estimated to be 20.7% (19.5% for brucellosis). The brucellosis IDR decreased between 1964 and 2008 and was higher during early post‐graduation. The risk of brucellosis was associated with the number of years of practice and the geographical area. Sixty‐nine respondents had at least one day of absence from work (24.0 ± 27.8 days). Conclusions A high frequency of zoonoses was reported by veterinarians with a large animal practice. Although the rate of zoonoses may be decreasing, further studies are needed to confirm this finding. A joint effort of all institutions is needed to prevent zoonoses among private practitioners.